A controllable gradient structure of hydrophobic composite fabric constructed by silver nanowires and polyvinylidene fluoride microspheres for electromagnetic interference shielding with low reflection. (May 2022) - Jia, Li; Ding, Xin; Sun, Jun; Zhang, Xian; Tian, Xingyou
Graphical abstract: Highlights: Excellent electromagnetic interference shielding fabrics with low surface reflection. Negative PVDF microspheres gradient provided good hydrophobic surface. Positive gradient structure of silver nanowires ensured the good EMI shielding performance. Abstract: Electromagnetic interference (EMI) shielding fabrics with high electrical conductivity generally could result in massive reflection and secondary EM radiation pollution. It is necessary to develop excellent EMI shielding fabrics with low surface reflection. A flexible EMI cotton composite with good hydrophobic performance was realized by constructing positive silver nanowires (AgNWs) gradient and negative poly(vinylidene fluoride) (PVDF) microspheres gradient via simple dip-coating method, which was automatically formed because of the gravity effect. The positive gradient structure of AgNWs ensured the good EMI shielding performance with a low surface reflection loss. The EMI shielding effectiveness (SE) values of Cotton/AgNWs/PVDF@GO composite fabrics exceeded 50 dB with power coefficient of reflectivity of only 0.39 at 10 GHz. Meanwhile, the negative PVDF microspheres gradient provided a hydrophobic surface on cotton. This work provides a novel strategy for fabricating EMI shielding fabrics with low reflection and high hydrophobic performance that suitable for application in wearable and portable electronic devices.